An e-Research approach to web-scale music analysis - De Roure, D; Page, K; Fields, B; Crawford, T; Downie, J; Fujinaga, I (Royal Society, 2011)
The growing quantity of digital recorded music available in large-scale resources such as the Internet Archive provides an important new resource for musical analysis. An e-Research approach has been adopted in order to create a very substantive web-accessible corpus of musical analyses in a common framework for use by music scholars, students and beyond, and to establish a methodology and tooling which will enable others to add to the resource in the future. The enabling infrastructure brings together scientific workflow and Semantic Web technologies with a set of algorithms and tools for extracting features from recorded music. It has been used to deliver a prototypical system, described here, that demonstrates the utility of Linked Data for enhancing the curation of collections of music signal data for analysis and publishing results that can be simply and readily correlated to these and other sources. This paper describes the motivation, infrastructure design and the proof-of-concept case study, and reflects on emerging e-Research practice as researchers embrace the scale of the Web.